Ecohydrological differences in peatlands under contrasting land use management systems in Eswatini - Thandeka Ndlela; Heinz Beckedahl; Piet-Louis Grundling; Stephan Glatzel; Mike Butler (Wetlands Ecology and Management, 2025)
Peatlands are vital ecosystems that regulate water flow, sequester carbon and support biodiversity. They are indispensable to many rural communities in southern Africa, providing essential ecosystem goods and services. However, their ecohydrological balance is vulnerable to both anthropogenic and natural disturbances. This study compares two peatlands in Eswatini, Malolotja (within a protected area) and Motjane (a community-managed site), to assess differences in peat stratigraphy, ecohydrological dynamics and water chemistry. By utilising groundwater wells, piezometers, stable isotope ratios and hydrochemical analyses across multiple transects, the study evaluates how land use, geomorphology and site history influence peatland ecohydrological functioning under similar climatic conditions. Findings indicate that Motjane, affected by drainage and grazing, experiences greater peat decomposition, fluctuating water tables and hydrochemical signs of disturbance. In contrast, Malolotja maintains a more stable water table and shows less peat degradation. Despite the contrasting land use contexts, both peatlands are primarily sustained by groundwater inputs, highlighting the critical role of subsurface hydrology in maintaining peatland function under pressure. The findings contribute towards understanding the complex interactions driving peatland ecohydrology and offer insights for targeted restoration and conservation strategies in Eswatini and the broader southern African region.